Thyroid Surgery in Children: A 5-Year Retrospective Study at a Single Paediatric Surgical Center and Systematic Review - Svetlana Bukarica; Jelena Antić; Ivana Fratrić; Dragan Kravarušić; Miloš Pajić; Radoica Jokić (MDPI AG, 2022)
The aim of this study was to analyse and evaluate our 5-year experience in paediatric thyroid surgery, as well as the specificities of this kind of surgery in the literature. This retrospective study was based on 19 operations in 17 patients aged from 5 to 17 years who were operated on due to thyroid pathology from 2017 until 2022. We presented data on surgical procedures and complications following surgery. Most of the patients were adolescent girls. The most common clinical presentations included enlarged thyroid gland, followed by thyroid nodules and hyperthyroidism. Eight total thyroidectomies, five left lobectomies, five right lobectomies, and three central neck dissections were performed. The most common histopathological diagnosis was hyperplastic diffuse colloid goitre, followed by papillary carcinoma, cystic nodule, follicular adenoma, Hashimoto thyroiditis and toxic adenoma. Postoperative course was uneventful, with four mild complications (one wound infection, one manifest hypocalcaemia, and two transitory recurrent laryngeal nerve paralysis). In our literature review, eighteen full-text articles were included and analysed. This study demonstrated that thyroid surgery in paediatric population is a safe and efficient procedure. Thyroid pathology in children significantly differs from that in the adults, and paediatric surgeons should be included into the team managing such cases.